Finance and Development, September 1967. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1967)
This paper focuses on the economic development in Taiwan. The paper highlights that it was under the Japanese that the first significant commercial development took place in Taiwan as the colony was transformed into a supplier of foodstuffs, particularly rice and sugar, for sale in Japan, in accordance with the normal views of that time of the role of a colonial dependency. The Japanese established an infrastructure in the form of power, communications, and water control systems. The last was an important contribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet